Developing Consequence Thresholds for Storm Models Through Participatory Processes: Case Study of Westerly Rhode Island - Witkop, Robert; Becker, Austin; Stempel, Peter; Ginis, Isaac (Frontiers in Earth Science, 2019)
Emergency managers face challenges in understanding and communicating potential hurricane hazards. Preparedness typically emphasizes the last event encountered, the potential implications of future hazards may thus be underestimated. Risk assessment models (e.g., basic HAZUS) that emphasize accumulated damages in economic terms do not provide actionable data regarding specific local concerns, such as access by emergency vehicles and potential communications disruptions. Qualitative methods conventionally used to identify these concerns, however, lack the specificity necessary to incorporate the managers’ knowledge into hazard models (e.g., highly exact geographic location of the vulnerability or cascading consequences). This research develops a method to collect rich, actionable, qualitative data from critical facility managers that can be utilized in combination with hydrodynamic, wind, and precipitation models to assess potential hazard consequences. A pilot study was conducted with critical facility managers in Westerly, Rhode Island USA, using semi-structured interviews and participatory mapping. Interview methods were based on existing practices for vulnerability assessments, and further augmented to obtain data based on hurricane modeling requirements. This research identifies challenges and recommendations when collecting critical facility manager's knowledge for incorporation into storm simulations. The method described and enables local experts to contribute actionable knowledge to natural hazard models and augment more traditional engineering-based approaches to risk assessment.